Tuberculosis in Chai Nat General Hospital - Anahanlipaiboon, Sukruethai (Journal of Health Science of Thailand, 2018)
Tuberculosis becomes a re-emererging disease and propagating a crisis in Thailand. This retrospective analytical study compared 214 pulmonary tuberculosis cases with 32 extrapulmonary tuberculosis registered in 246 medical records from January 1, 2007 to December 31, 2007 and their differences were tested with chi-square. It was reported that 64.63 percent of them were male. Their average age was 55.43 (SD 17.55) years with the dominance of the 30-44 year age group. The two groups differed in age distribution significantly (p< 0.05). On average, the onset of symptoms was reportedly 2.96 (SD 5.43) days prior to their hospital visits and mean of length of hospital stay 7.99 (SD 7.29) days. The extrapulmonary group tended to stay longer in the hospital than the other significantly (p< 0.05). While the main sign and first-day symptom of the pulmonary tuberculosis was cough, the other group exhibited fever and weakness. Most cases of extrapulmonary tuberculosis were infected in lymph nodes. In both groups, hepatitis was commonly reported as a co-morbid disease. Only 37.8 percent of the total had sputum examined,37.86 percent of the specimens were positive. Whereas most of the pulmonary tuberculosis received 6-month regimen, the other group tended to receive over 6-month regimen significantly (p<0.05).